Analisis Kontrastif Bahasa Prancis dan Bahasa Inggris Sebagai Dasar Penentuan Model Pembelajaran Bahasa Prancis Pemula - Lestari, Dian; Endi, Ferhadius (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The study aimed to describe the similarities and differences of French and English verbs for designing for French learning models for beginners. This reseach is a qualitative descriptive study, the data were collected using observational method by taking notes directly from the data sources, and data were analyzed using distributional method. The result shows the similarity of French and English verbs as known from their verb formations by using the process of conjugation. French and English verbs are different where French is fully inflected while English is partially inflected. French verbs are influenced by person and number while English verbs are not influenced by person dan number. Past marker in French is auxiliary (être and avoir) followed by participe passé. The verb with auxiliare être will undergo a process of affixation with the addition of suffixes -e, -s, -es on the participe passé (core verb). Past marker in English is suffixe –ed/-d for regular verbs while irregular verbs will undergo changes based on the certain rules.